Reasons of Students Using Code Switching in English Language Teaching - Syarifah Rischa Nadya*; Rani Herning Puspita (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The purpose of this study was to determine why students employed code switching during the learning process in English class. Six students from SMKN 4 Samarinda in the 2021/2022 academic year participated in this study. The subjects were students with the greatest English score, the median English score, and the lowest English score. The English teacher contributed to the score. The descriptive qualitative method was used in this investigation. The data for the study was gathered through observation and interviews. Hoffman theory was used to examine the data. The study's findings revealed the reasons why students use code switching for repeat for explanation and interruption.